2007
DOI: 10.1038/nm1625
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Fas antagonism by Met in human fatty liver disease

Abstract: Hepatocytes in fatty livers are hypersensitive to apoptosis and undergo escalated apoptotic activity via death receptor-mediated pathways, particularly that of Fas-FasL, causing hepatic injury that can eventually proceed to cirrhosis and end-stage liver disease. Here we report that the hepatocyte growth factor receptor, Met, plays an important part in preventing Fas-mediated apoptosis of hepatocytes by sequestering Fas. We also show that Fas antagonism by Met is abrogated in human fatty liver disease (FLD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 34 publications
5
65
2
Order By: Relevance
“…Thus, it is speculated that proliferation of liver cells might be inhibited due to the intense stimulation of CCl 4 and alcohol in this study. The oncogene MET played an important part in preventing Fas-mediated apoptosis of hepatocytes (Zou et al, 2007), and proliferation and survival of hepatocytes were impaired in mice with Met mutants after partial hepatectomy (Borowiak et al, 2004). Consistent with the above results, this study showed that the down-regulation of MET at 9 weeks may activate cell death of hepatocytes and its up-regulation at 9 weeks may suppress proliferation of liver cells.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, it is speculated that proliferation of liver cells might be inhibited due to the intense stimulation of CCl 4 and alcohol in this study. The oncogene MET played an important part in preventing Fas-mediated apoptosis of hepatocytes (Zou et al, 2007), and proliferation and survival of hepatocytes were impaired in mice with Met mutants after partial hepatectomy (Borowiak et al, 2004). Consistent with the above results, this study showed that the down-regulation of MET at 9 weeks may activate cell death of hepatocytes and its up-regulation at 9 weeks may suppress proliferation of liver cells.…”
Section: Discussionsupporting
confidence: 87%
“…PARP1 and PARP2 proteins were first characterized as DNA repair factors that mainly respond to DNA damage and maintain the chromatin structure and integrity. Recent studies have established that PARPs serve as transcriptional enhancers and coactivators (24,34,35). Our functional experiments support the notion that C/EBP-β1 and PARPs cooperate with each other and activate the HGF gene promoter (Figure 6, A-C).…”
Section: Figuresupporting
confidence: 88%
“…This was verified by western blot using an antibody against PARP that recognizes both isoforms of PARP (PARP1 and PARP2; Figure 5D). PARPs are potent activators of gene transcription via their ability to open chromatin by polyribosylation of histones (24). We then investigated the effects of gradual loss of DATE truncation on C/EBP-β1 and PARPs binding to the promoter region to determine the minimum numbers of As that need to be deleted from DATE to enhance factor binding.…”
Section: Truncation Mutation Of Date In the Hgf Gene Promoter Region mentioning
confidence: 99%
See 1 more Smart Citation
“…MET also interacts with the death receptor Fas, which maintains homeostasis in many tissues. MET is able to prevent Fas-mediated apoptosis in hepatocytes by sequestering Fas Zou et al 2007). This is a novel relationship between growth factor receptors and cytokine receptors in controlling apoptosis.…”
Section: Gab1 Gab1 H G F / S F H G F / S F Hgf/sfmentioning
confidence: 99%